A New Thermal Categorization of Ice‐Covered Lakes. Issue 3 (3rd February 2021) - Yang, Bernard; Wells, Mathew G.; McMeans, Bailey C.; Dugan, Hilary A.; Rusak, James A.; Weyhenmeyer, Gesa A.; Brentrup, Jennifer A.; Hrycik, Allison R.; Laas, Alo; Pilla, Rachel M.; Austin, Jay A.; Blanchfield, Paul J.; et al.
Abstract: Lakes are traditionally classified based on their thermal regime and trophic status. While this classification adequately captures many lakes, it is not sufficient to understand seasonally ice‐covered lakes, the most common lake type on Earth. We describe the inverse thermal stratification in 19 highly varying lakes and derive a model that predicts the temperature profile as a function of wind stress, area, and depth. The results suggest an additional subdivision of seasonally ice‐covered lakes to differentiate underice stratification. When ice forms in smaller and deeper lakes, inverse stratification will form with a thin buoyant layer of cold water (near 0°C) below the ice, which remains above a deeper 4°C layer. In contrast, the entire water column can cool to ∼0°C in larger and shallower lakes. We suggest these alternative conditions for dimictic lakes be termed "cryostratified" and "cryomictic." Plain Language Summary: Most mid and high latitude lakes are seasonally ice‐covered and have only been classified based on the thermal structure and trophic status during the open‐water season in summer. However, limited temperatures observations in these ice‐covered lakes suggest that there is a wide range of thermal structures over winter. We developed an analytical model to predict the average water temperature at the time of ice formation based on the strength of the surface winds, the area of the lake, and the maximum depth of the lake. Using both the analytical model and water temperature data from 19 different lakes in North America, Europe, and Asia, we found that the time of ice formation in lakes that are large or experience strong winds were later compared to lakes that are small or experience weak winds. The larger and windier lakes are also colder (0°C∼2°C) than smaller and calmer lakes (2°C∼4°C) at the time of ice formation. This suggests that these seasonally ice‐covered lakes can be subdivided into two additional classes during winter. The analytical model and the new categorization have important consequences for understanding fish habitat under the ice and the potential effects of climate change on these seasonally ice‐covered lakes. Key Points: Standard classifications of dimictic lakes do not consider how variable the initial thermal stratification can be under winter lake ice Lakes that are shallow or windy can cool to near 0°C–1°C before ice forms and are weakly stratified, which we term "cryomictic" Deeper lakes or those with calmer winds, result in ice forming just above deeper waters of 3°C–4°C, which we term "cryostratified"